(untitled) (UNIZIK Journal of STM Education, 2024)
The study assessed the perception of teachers on the disciplinary problems faced by secondary school students and the measures adopted by teachers in disciplining erring students. Research design adopted was descriptive survey. Participants of the study consists of 684 teachers (189 males and 495 females) from public secondary schools in Enugu state of Nigeria selected through disproportionate stratified and simple random sampling techniques. The researcher used self-constructed questionnaire captioned disciplinary problems and measures of secondary school students (DPMSSS) to collect data for the study. Three experts validated the instrument. Reliability co-efficient of the instrument is .79, obtained using Cronbach alpha method. Data collected were analyzed using mean and standard deviation.Result indicated that disciplinary problems of students in secondary schools are examination malpractice, stealing, lateness to school, absenteeism, and bullying/fighting, wrong use of cell phones, vandalism, truancy, sexual harassments and insulting of teachers. The disciplinary measures adopted by teachers in secondary schools include verbal warning, referral to principal, referral to disciplinary committee, written warning, and suspension, loss of privileges, manual labour, counseling/therapy, and flogging, discussion, kneeling down and reporting to parents. Gender of the teacher influences disciplinary measures adopted in secondary schools. Whereas the male teachers adopt verbal warning, manual labour and flogging to a very high extent, the female teachers adopt counselling to a very high extent. The research recommends that teachers should adopt a combination of the above measures, melt appropriate and commensurate punishment out to erring students to serve as deterrent to other students.